A novel test technique for the mechanistic study of initiation of environmentally assisted cracking on a Ni–30Cr–10Fe alloy in simulated pressurized water reactor primary water. (December 2020) - Kuang, Wenjun; Yue, Han; Feng, Xingyu; Yang, Bo; Guo, Chaowei
Abstract: Recurring step straining was developed to investigate the environmentally assisted cracking (EAC) initiation of a Ni-30Cr-10Fe alloy (Alloy 690) in simulated pressurized water reactor (PWR) primary water. Thanks to this technique, the roles of corrosion and straining in the EAC initiation of Alloy 690 was decoupled and typical microstructures in stress corrosion cracking, i.e. diffusion induced grain boundary migration and oxidation into the migration zone, were reproduced. Digital image correlation using indigenous surface oxide particles as markers was successfully incorporated into this technique for high-resolution in-plane strain measurement. The preliminary results show that intergranular crack initiation is correlated with the high local strain in both adjacent grains, indicating that slip transfer across the grain boundary promotes crack initiation. Recurring step straining is desirable for the mechanistic study of EAC as it makes the separate roles of chemical and mechanical processes adjustable and traceable. Graphical abstract: Image, graphical abstract